Increasing pursuer capturability by using hybrid dynamics - Glizer, Valery Y.; Turetsky, Vladimir (Zielona Góra: Uniwersytet Zielonogórski)
A robust interception of a maneuverable target (evader) by an interceptor (pursuer) with hybrid dynamics is considered. The controls of the pursuer and the evader are bounded. The duration of the engagement is prescribed. The pursuer has two possible dynamic modes, which can be switched once during the engagement, while the dynamics of the evader are fixed.
Keywords: interception problem; hybrid interceptor`s dynamics; robust capture zone